Using photovoice as an arts-based method for grieving: LGBTQ + students and the pulse nightclub shooting. Issue 5 (28th May 2021) - Suárez, Mario I.; Asadi, Lobat; Scaramuzzo, Peter; Slattery, Patrick; Mandala, Chad R.
Abstract: Given the increase of gun violence in the United States, teachers are left with the added obligation of helping students process traumatic events. The present study seeks to address the following questions: What are some ways in which students process grief through arts-based methods? What can we observe through photovoice, a community-based method that uses photography, about the perceptions of six LGBTQ + students at a predominantly white institution after the Pulse Massacre? The study consisted of semi-structured focus group interviews with these students, all of whom spent a week creating photos in response to the tragedy. In order to understand the depth of how stories may have oppositional counter-stories, we look to narrative inquiry and find intersectionality and colorblind intersectionality at play. Implications for practice, policy, and research are included.